ANALISIS PERKEMBANGAN KASUS KORUPSI DAN PERAN KOMISI PEMBERANTASAN KORUPSI DALAM PEMBERANTASAN KASUS KORUPSI DI INDONESIA SERTA STUDI KASUS FIRLI BAHURI - Charyza Najma Divania; Indah Aprilia; Nathan Egbert Latuheru; Reynaldi Arrayan Isa (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Corruption has become a disease that continues to take root in the process of state administration. The feeling of greed for more power and wealth and the opportunity to become one of the factors of corruption is still carried out. Apart from that, the lack of strong supervision from supervisory institutions and the lack of strong sanctions given to perpetrators of corruption increasingly embolden them to choose this path. In the eradication process, state institutions have been established, such as the Prosecutor's Office and the Police. However, due to the lack of power in resolving the corruption cases that occurred, an independent state institution to eradicate corruption was formed through Law Number 30 of 2003, commonly known as the Corruption Eradication Commission (KPK). As a new institution, the Corruption Eradication Committee does not have a truly independent task in the process of eradicating corruption. The Corruption Eradication Committee (KPK) must continue to cooperate with the Prosecutor's Office and the Police to eradicate corruption cases. This collaboration is intended to create a more efficient and effective corruption eradication process. As an independent institution, the KPK is also required not to involve the interests of any institution in carrying out its duties, including the interests of its own institution.